The effect of titanium dioxide filler on soft liners on Candida albicans growth and surface hardness - Aditama, Pramudya; Indrastuti, Murti; Ruspita, Intan (Majalah Kedokteran Gigi Indonesia, 2024)
Soft liners are recommended in denture stomatitis, yet they are prone to microorganism colonization. Modification of soft liners can be done by adding titanium dioxide (TiO2) because they induce photocatalytic production and increase the physical strength of the material. This research aims to examine the effect of adding (TiO2) filter in soft liners on the growth of Candida albicans and surface hardness. This research used disc-shaped soft liners with 2 sizes: 10 mm in diameter and 2 mm in thickness for the mold growth test and 10 mm in diameter and 6mm in thickness for surface hardness. Each of the 24 samples was divided into 4 groups: groups I, II, and III with the addition of (TiO2) at concentrations of 0.5%, 1%, and 2%, respectively, and group IV acting as the control group without (TiO2). Test of the growth of Candida albicans used dilution method, and calculations were made with a colony counter. Test of surface hardness used a durometer, and data were analyzed using one-way ANOVA and LSD. The results showed that among the groups, group III demonstrated the lowest growth of Candida albicans (7.67±2.25 x103CFU/mL), while group IV exhibited the highest growth (21.33±4.63 x103CFU/ml). The results of the ANOVA test showed that the addition of TiO2 had a significant effect on the growth of Candida albicans (p < 0.05). In the LSD test, there were significant differences between the control group and all of the treatment groups. In the surface hardness test, the highest was observed in group III (29.92 ± 1.52 HA), and the lowest was in group IV (23.08 ± 2.6 HA). The results of the ANOVA test indicated the effect of adding (TiO2) on the hardness of the soft liners (p < 0.05). The LSD test showed significant differences between the control group and all of the treatment groups. The addition of 0.5%-2% (TiO2) concentrations to soft liners inhibited the growth of Candida albicans, while the 0.5% concentration showed the smallest change in surface hardness.